Sosialisasi QRIS Dalam Upaya Peningkatan Produktivitas UMKM Provinsi DKI Jakarta - Antyo Pracoyo; Paulina Paulina; Erric Wijaya; Wasi Bagasworo; Whony Rofianto (LPMP Imperium, 2022)
The objectives of this activity include: exploring the problems faced by MSMEs during the second year of the Covid-19 pandemic; identify problems that occur in MSMEs in DKI Jakarta in a pandemic condition (New Normal); provide an overview and training in making QRIS for MSMEs in DKI Jakarta; provide strategic management tips so that they can survive and even develop unexpected opportunities; provide continuous assistance and monitoring to MSMEs assisted by P3D which have been carried out after entering the New Normal period. QRIS socialization is one of the efforts made by the government to respond to the changes that occur, especially to the very rapid development of information technology. QRIS socialization was carried out for MSME actors in the DKI Jakarta area in collaboration with Bank Indonesia Jakarta Branch, P3D DKI Jakarta. The method used in this activity is in the form of socializing the use of QRIS which will be applied by Bank Indonesia to MSME players in the DKI Jakarta area. In this outreach activity, MSME participants received training on: how to solve problems, entrepreneurship, digital transformation, and change management.